Overexpression of cytoplasmic C4Flaveria bidentis carbonic anhydrase in C3Arabidopsis thaliana increases amino acids, photosynthetic potential, and biomass. Issue 8 (12th June 2022) - Kandoi, Deepika; Ruhil, Kamal; Govindjee, Govindjee; Tripathy, Baishnab C.
Summary: An important method to improve photosynthesis in C3 crops, such as rice and wheat, is to transfer efficient C4 characters to them. Here, cytosolic carbonic anhydrase (CA: βCA3 ) of the C4 Flaveria bidentis ( Fb ) was overexpressed under the control of 35 S promoter in Arabidopsis thaliana, a C3 plant, to enhance its photosynthetic efficiency. Overexpression of CA resulted in a better supply of the substrate HCO 3 ‐ for the endogenous phosphoenolpyruvate carboxylase in the cytosol of the overexpressers, and increased its activity for generating malate that feeds into the tricarboxylic acid cycle. This provided additional carbon skeleton for increased synthesis of amino acids aspartate, asparagine, glutamate, and glutamine. Increased amino acids contributed to higher protein content in the transgenics. Furthermore, expression of FbβCA3 in Arabidopsis led to a better growth due to expression of several genes leading to higher chlorophyll content, electron transport, and photosynthetic carbon assimilation in the transformants. Enhanced CO2 assimilation resulted in increased sugar and starch content, and plant dry weight. In addition, transgenic plants had lower stomatal conductance, reduced transpiration rate, and higher water‐use efficiency. These results, taken together, show that expression of C4 CA in the cytosol of a C3 plant can indeed improve its photosynthetic capacity with enhanced water‐use efficiency. Abstract : The cytosolic FbβCA3 having low Km for CO2 increase the hydration of CO2 . The dashed arrows indicate the diffusion of CO2 within the cytosol and the organells. FbβCA3 overexpression increased the flux of the carboxylic acid to the tricarboxylic acid cycle (TCA) in mitochondria to play an an ansplerotic role to synthesize higher amounts of total amino acids and proteins that contribute to increase photosynthetic efficiency and biomass (OAA ‐ oxaloacetic acid; PEP ‐ phoshoenol pyruvate; PEPC ‐ phosphoenolpyruvate carboxylase; TCA cycle ‐ tri carboxylic acid cycle).